2011
DOI: 10.1167/iovs.10-6033
|View full text |Cite
|
Sign up to set email alerts
|

Submacular DL-α-Aminoadipic Acid Eradicates Primate Photoreceptors but Does Not Affect Luteal Pigment or the Retinal Vasculature

Abstract: Submacular injection of DL-α-AAA induced severe damage to photoreceptors but failed to eliminate Müller cells in monkeys. Central macular pigment persisted despite loss of photoreceptors, and the retinal vasculature was unaffected. These observations may have significance in studying the roles of different cellular components in the pathogenesis of MT2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…20 Higher concentrations of LAA have also been shown to be nontoxic to in vitro endothelial cells and pericytes. 27 It should be noted that, because glial cells provide structural and metabolic support for neurons, depletion of retinal glial cells may cause neuronal malfunction, which in turn affects their interaction with the vasculature. However, Song et al 20 showed that 24 hours after intravitreal injection of LAA, retinal function remained normal as examined using electroretinography.…”
Section: Discussionmentioning
confidence: 99%
“…20 Higher concentrations of LAA have also been shown to be nontoxic to in vitro endothelial cells and pericytes. 27 It should be noted that, because glial cells provide structural and metabolic support for neurons, depletion of retinal glial cells may cause neuronal malfunction, which in turn affects their interaction with the vasculature. However, Song et al 20 showed that 24 hours after intravitreal injection of LAA, retinal function remained normal as examined using electroretinography.…”
Section: Discussionmentioning
confidence: 99%
“…Macular pigment is located in Henle's layer (Snodderly et al, 1984a(Snodderly et al, , 1984bTrieschmann et al, 2008), but whether it is associated with nerve fibers of photoreceptors or Müller cell processes remains unknown. Macular pigment appeared to persist when primate photoreceptors were ablated by subretinal alpha-aminoadipic acid in a primate study, suggesting that at least some of the pigment may reside in Müller cells, which were relatively unaffected in this model (Shen et al, 2011). Analysis of the central retina from the fellow eye of this pair using proteomic techniques revealed reduced levels of Müller cellspecific proteins, including glial fibrillary acid protein, vimentin and glutamine synthetase (Len et al, 2012).…”
Section: The Role Of Müller Cellsmentioning
confidence: 85%
“…To overcome the barrier properties of RPE and the retinal inner limiting membrane, subretinal injection can be utilized. Subretinal administration of DL-AAA can alter the blood-retinal barrier in rats and eliminate photoreceptors in monkeys 33, 44 . Our results suggested that ERG a-waves and the expression of GS reduced at 7 days after subretinal injection of 70 μg/μl DL-AAA to the rats.…”
Section: Discussionmentioning
confidence: 99%
“…DL-α-aminoadipate (DL-AAA) was prepared in accordance with established procedures 32, 33, 44, 60 . Different concentrations of DL-AAA solution (7 μg/μl to 140 μg/μl) were injected into the subretinal space under dim-red light (wavelength >620 nm).…”
Section: Methodsmentioning
confidence: 99%